The Effect of Capital Structure and Profitability on Company Value in the Food and Beverage Sector in Indonesia - Yunita, Lia; Ridloah, Siti; Humaira, Hanina (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
The value of the company has a direct impact on the maximum shareholder prosperity if the company's share price increases and this value also reflects the extent to which the company is recognized by the public. This study aims to examine the effect of capital structure and profitability on firm value. The population of this research is the manufacturing companies in the food and beverage sub-sector which are listed on the Indonesia Stock Exchange for the 2017-2021 period, while the sample is 33 companies using purposive sampling technique, so the number of observations was 165 data. The data analysis method used panel data regression analysis with an analytical tool in the form of Eviews 10. The results of this study indicate that capital structure (DER) has a negative and significant effect on firm value, then profitabily (ROE) has a positive and significant effect on firm value.